1991
DOI: 10.2134/agronj1991.00021962008300020015x
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Fixation and Nitrogen Balance in Cool‐Season Food Legumes

Abstract: Understanding the magnitude of N2 fixation and export of plant N, particularly in the harvested grain and straw, is necessary to assess the potential for grain legumes to contribute to long‐term agricultural production stability. The proportions of total plant N derived from N2 fixation in four grain legume crops, faba bean (Vicia faba L.), chickpea (Cicer arietinum L.), lentil (Lens culinaris L), and pea (Pisum sativum L.), were estimated in three field experiments conducted for two seasons in Syria (Vertic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 18 publications
(23 reference statements)
5
46
0
3
Order By: Relevance
“…Although some authors have reported that chickpeas are capable of fixing all the N they need (Mahler et al 1988), others have reported that the crop does not fix adequate N for maximum growth even when vigourous nodules are present (Beck et al 1991 ). This work indicates that in Canterbury, whether the crop is inoculated with suitable Rhizobium or not, N fertiliser is required for maximum growth and yield.…”
Section: Nitrogenmentioning
confidence: 81%
See 1 more Smart Citation
“…Although some authors have reported that chickpeas are capable of fixing all the N they need (Mahler et al 1988), others have reported that the crop does not fix adequate N for maximum growth even when vigourous nodules are present (Beck et al 1991 ). This work indicates that in Canterbury, whether the crop is inoculated with suitable Rhizobium or not, N fertiliser is required for maximum growth and yield.…”
Section: Nitrogenmentioning
confidence: 81%
“…Chickpeas are not considered strong N fixers even when adequate nodules are present. Beck et al ( 1991 ) reported that chickpeas obtained from 8-81 % of their plant N requirements from fixed atmospheric N. The amount depended on both the site and time of sowing.…”
Section: H94060 Received 31 August 1994; Accepted 31 August 1995mentioning
confidence: 99%
“…For instance, values for N2 fixation were high and there was a small net contribution of fixed N to soil following seed harvest of winter sown chickpea in Syria (Table 8), whereas both crop N and Pfix were low in spring sowings where drought limited growth as early as anthesis. In contrast, in France, differences between N2 fixed by winter-sown and spring-sown chickpea were still observed, but were not so marked because of extended moisture availability throughout the later stages of growth (Beck et al, 1991; Table 8). …”
Section: Time Of Sowingmentioning
confidence: 94%
“…For cool-season food legumes, Beck et al [2] concluded that even if the drought stress effects on N 2 fixation do not always directly affect grain yield, drought may result in a significant decrease in the total N balance.…”
Section: Introductionmentioning
confidence: 99%